Involvement of Phosphodiesterase 2A Activity in the Pathophysiology of Fragile X Syndrome. (23rd August 2018) - Maurin, Thomas; Melancia, Francesca; Jarjat, Marielle; Castro, Liliana; Costa, Lara; Delhaye, Sébastien; Khayachi, Anouar; Castagnola, Sara; Mota, Elia; Di Giorgio, Audrey; Servadio, Michela; Drozd, Malgorzata; et al.
Abstract: The fragile X mental retardation protein (FMRP) is an RNA-binding protein involved in translational regulation of mRNAs that play key roles in synaptic morphology and plasticity. The functional absence of FMRP causes the fragile X syndrome (FXS), the most common form of inherited intellectual disability and the most common monogenic cause of autism. No effective treatment is available for FXS. We recently identified the Phosphodiesterase 2A ( Pde2a ) mRNA as a prominent target of FMRP. PDE2A enzymatic activity is increased in the brain of Fmr1 -KO mice, a recognized model of FXS, leading to decreased levels of cAMP and cGMP. Here, we pharmacologically inhibited PDE2A in Fmr1 -KO mice and observed a rescue both of the maturity of dendritic spines and of the exaggerated hippocampal mGluR-dependent long-term depression. Remarkably, PDE2A blockade rescued the social and communicative deficits of both mouse and rat Fmr1- KO animals. Importantly, chronic inhibition of PDE2A in newborn Fmr1 -KO mice followed by a washout interval, resulted in the rescue of the altered social behavior observed in adolescent mice. Altogether, these results reveal the key role of PDE2A in the physiopathology of FXS and suggest that its pharmacological inhibition represents a novel therapeutic approach for FXS.